Sedative-Hypnotics Are Widely Abused by Drivers Apprehended for Driving Under the Influence of Drugs. Issue 3 (June 2015) - Kriikku, Pirkko; Hurme, Hannes; Wilhelm, Lars; Rintatalo, Janne; Hurme, Jukka; Kramer, Jan; Ojanperä, Ilkka
Abstract : Background: Sedative-hypnotics are commonly encountered in drivers apprehended for driving under the influence of drugs (DUID). Previous research has mainly concentrated on the residual effects of the drugs. Methods: In this study, the extent of sleep medication use and abuse among drivers apprehended on suspicion of DUID was assessed. Additionally, the prevalence and concentrations of the drugs, concomitant use of other drugs of abuse, and the age and sex of the drivers positive for the most commonly prescribed sedative-hypnotics (temazepam, midazolam, nitrazepam, zopiclone, and zolpidem) in DUID cases in Finland in 2009 to 2011 were examined. Results: Sedative-hypnotics were found in 3155 samples of the 13, 248 that were analyzed. Temazepam was present in over half of the cases (57.9%), along with other benzodiazepines such as midazolam (13.1%) and nitrazepam (7.0%) and the non-benzodiazepine hypnotics zopiclone (12.2%) and zolpidem (9.8%). The mean age of the drivers using the studied sedative-hypnotics was 33.5 years. Many of the drivers were polydrug users; concomitant stimulant use was found in nearly half of the cases. Cannabis and alcohol were also very common co-findings. In nearly 20% of the cases, the driver had taken more than 1 of the studied sedative-hypnotics; only 2.5% had no findings other than a single sedative-hypnotic in their blood. The drug use pattern of those positive for zopiclone and zolpidem was somewhat different from that of users of benzodiazepine sedative-hypnotics; their age was higher and the concomitant use of illegal stimulants was markedly less prevalent than among the users of temazepam, midazolam, and nitrazepam. Conclusions: There were very few cases in our study population where the positive sedative-hypnotic finding could have been due to appropriate medical use. The extremely prevalent concomitant use of other psychoactive drugs and the high median serum concentrations of the studied sedative-hypnotics suggest their widespread abuse among apprehended drivers.